2002
DOI: 10.1006/jmva.2001.1989
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation for Controlled Semilinear Stochastic Systems: Identifiability and Consistency

Abstract: We consider a controlled stochastic semilinear evolution equation with the drift depending on the unknown parameter. We show that the maximum likelihood estimator is strongly consistent for a class of bounded predictable controls. 2001Elsevier Science AMS 1991 subject classifications: 62M09; 62M40; 93E10; 93E35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…He also investigated the asymptotic properties of the maximum likelihood estimator and the Bayes estimator of the drift parameter in stochastic equations driven by fractional Brownian motion, see [23] and [24]. Goldys and Maslowski considered in [7] a controlled stochastic semilinear equation with the drift depending on the unknown parameter and with the Wiener process as the driving process. They showed that the maximum likelihood estimator is consistent for a class of bounded predictable controls.…”
Section: Introductionmentioning
confidence: 99%
“…He also investigated the asymptotic properties of the maximum likelihood estimator and the Bayes estimator of the drift parameter in stochastic equations driven by fractional Brownian motion, see [23] and [24]. Goldys and Maslowski considered in [7] a controlled stochastic semilinear equation with the drift depending on the unknown parameter and with the Wiener process as the driving process. They showed that the maximum likelihood estimator is consistent for a class of bounded predictable controls.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the only work on estimation of the nonlinearity in semilinear SPDEs was conducted by Goldys and Maslowski [22] who studied a parametric problem, assuming a full observation (X t ) t≤T of a controlled SPDE as T → ∞. Somewhat related, Pasemann et al [40] studied estimation of the diffusivity parameter when the nonlinearity is only known up to a finite-dimensional nuisance parameter by using a joint maximum likelihood approach for spectral observations.…”
Section: Introductionmentioning
confidence: 99%
“…[Kut04] and references therein. We will omit this analysis here, and for more details specific to SPDEs, we refer the reader to [LR17,CX15] for the spectral approach, to [KL85,Log84] for non-spectral approach, and to [GM02] for controlled SPDEs. As already mentioned, with the idea of approximating a singular model by regular models, in the spectral approach, we will take the large number of Fourier modes asymptotics, N → ∞, which will be one of the main focuses of this paper; see Section 2.…”
Section: Introductionmentioning
confidence: 99%